2022
DOI: 10.3390/cells11020222
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells and Cancer Immunotherapy

Abstract: Despite largely disappointing clinical trials of dendritic cell (DC)-based vaccines, recent studies have shown that DC-mediated cross-priming plays a critical role in generating anti-tumor CD8 T cell immunity and regulating anti-tumor efficacy of immunotherapies. These new findings thus support further development and refinement of DC-based vaccines as mono-immunotherapy or combinational immunotherapies. One exciting development is recent clinical studies with naturally circulating DCs including plasmacytoid D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 130 publications
(212 reference statements)
0
30
0
1
Order By: Relevance
“…As the most effective antigen-presenting cells (APCs), DCs play an essential role in initiating persistent innate and adaptive immunity and are of great significance in the body’s immune function and tumor immune management. , DC-derived exosomes are tiny vesicles secreted by sentinel APCs of the immune system, carrying DC antigens such as functional MHC-antigenic complexes and T cells costimulatory molecules, which participate in specific cytotoxic T lymphocyte (CTL) responses to inhibit tumor growth. , Tumor-infiltrating DCs can convey tumor-related antigens to effector T cells, promote memory T cells to induce differentiation, enhance the therapeutic effects of immune checkpoint inhibitors, and finally prevent recurrence of tumors. , Recently, considerable emphasis has been paid to the role of DC-derived exosomes in tumor immunity, and the clinical trials based on DC-derived exosomes have proven their potential practicality in cancer therapy. , Indeed, the tumor-peptide-pulsed DC-derived exosomes have been used as antitumor vaccines to treat cancers and show encouraging efficacy in the preclinical trials. , …”
Section: Immune Cell-derived Exosomes In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…As the most effective antigen-presenting cells (APCs), DCs play an essential role in initiating persistent innate and adaptive immunity and are of great significance in the body’s immune function and tumor immune management. , DC-derived exosomes are tiny vesicles secreted by sentinel APCs of the immune system, carrying DC antigens such as functional MHC-antigenic complexes and T cells costimulatory molecules, which participate in specific cytotoxic T lymphocyte (CTL) responses to inhibit tumor growth. , Tumor-infiltrating DCs can convey tumor-related antigens to effector T cells, promote memory T cells to induce differentiation, enhance the therapeutic effects of immune checkpoint inhibitors, and finally prevent recurrence of tumors. , Recently, considerable emphasis has been paid to the role of DC-derived exosomes in tumor immunity, and the clinical trials based on DC-derived exosomes have proven their potential practicality in cancer therapy. , Indeed, the tumor-peptide-pulsed DC-derived exosomes have been used as antitumor vaccines to treat cancers and show encouraging efficacy in the preclinical trials. , …”
Section: Immune Cell-derived Exosomes In Cancer Therapymentioning
confidence: 99%
“…69,70 Recently, considerable emphasis has been paid to the role of DC-derived exosomes in tumor immunity, and the clinical trials based on DC-derived exosomes have proven their potential practicality in cancer therapy. 71,72 Indeed, the tumor-peptide-pulsed DCderived exosomes have been used as antitumor vaccines to treat cancers and show encouraging efficacy in the preclinical trials. 73,74 Viaud et al originally reported that DC-derived exosomes transferred functional MHC-antigenic complexes (classes I and II) to DCs and promoted the activation of CD8 + and CD4 + T cells, respectively (Figure 4A,B).…”
Section: Immune Cell-derived Exosomes In Cancer Therapymentioning
confidence: 99%
“…Among the professional antigen-presenting cells are dendritic cells. Dendritic cells are divided into dendritic cells type 1 (DC1) and type 2 (DC2) [ 23 ]. DC1 express CD11 and have a myeloid morphology.…”
Section: Infusion Of Autograft-professional Antigen-presenting Cellsmentioning
confidence: 99%
“…DC1 express CD11 and have a myeloid morphology. When DC1 are stimulated by tumor necrosis factor, DC1 produce high levels of interleukin 12 (IL-12) causing antigen-naïve CD4 to differentiate into T helper type 1 cells [ 23 ]. T helper type 1 cells secret interferon-gamma and tumor necrosis factor-alpha leading to the activation and development of cytotoxic T cells.…”
Section: Infusion Of Autograft-professional Antigen-presenting Cellsmentioning
confidence: 99%
See 1 more Smart Citation